Policy recommendations for community empowerment in climate change adaptation: A study of the Go Green Pandawara Group campaign in Support of SDG 13 Climate Action - Harmono Fendi; Nurhamzah Fachrizal (E3S Web of Conferences)
This research aims to formulate policy recommendations for community empowerment in facing climate change through a case study of the Go Green campaign conducted by the Pandawara Group in alignment with SDG 13: Climate Action. This campaign focuses on raising public awareness about the importance of climate change adaptation efforts through concrete actions such as reforestation, waste management, and carbon footprint reduction. The method used in this research is a qualitative approach with case study analysis. Data were collected through interviews, observations, and documentation of campaign activities. The study results show that the Go Green campaign by the Pandawara Group successfully encouraged active community participation in various environmentally friendly programs. However, there are challenges to the program's sustainability, particularly related to long-term commitment and more robust policy support from the government. Therefore, this research provides several policy recommendations, including strengthening collaboration between the government, communities, non-governmental organisations, and the private sector and integrating climate change adaptation programs into regional development plans. Implementing these policies is expected to strengthen the community’s capacity to face the impacts of climate change.